Hearing loss is associated with cortical thinning in cognitively normal older adults. (8th April 2020) - Ha, J.; Cho, Y. S.; Kim, S. J.; Cho, S. H.; Kim, J. P.; Jung, Y. H.; Jang, H.; Shin, H.‐Y.; Lin, F. R.; Na, D. L.; Seo, S. W.; Moon, I. J.; et al.
Abstract : Background and purpose: Hearing loss (HL) is one of the most influential risk factors of dementia in older adults. However, its potential association with neurodegeneration is not well established. The association between HL and cortical thickness in cognitively normal older adults was evaluated. Methods: In all, 982 cognitively normal older adults (age ≥65 years) were identified from the Health Promotion Center at the Samsung Medical Center from September 2008 to December 2014. The participants underwent pure‐tone audiometry and brain magnetic resonance imaging. HL was evaluated according to a four‐frequency (0.5, 1, 2, 4 kHz) pure‐tone average. Participants were divided into three groups according to pure‐tone average (normal hearing ≤15 dB, minimal HL 16–25 dB, mild‐to‐severe HL >25 dB). Cortical thickness in the HL groups was compared with that of the normal hearing group. Results: In women, right ear HL was associated with cortical thinning: the minimal HL group showed cortical thinning in the left frontal and bilateral occipital areas and the mild‐to‐severe HL group showed cortical thinning in the bilateral frontal, right temporal and bilateral occipital areas compared to the normal hearing group. In men, there was no significant association between HL on either side and cortical thickness. Conclusion: In older women, right ear HL is associated with neurodegeneration even in a cognitively normal state. Therefore, managing HL especially in older women may be an effective strategy for dementia prevention.